Relación entre violencia familiar y el rendimiento académico en estudiantes: Opinión de experto - Ochoa Osorio, Sergio Iván (Universidad Antonio Nariño, 2024)
English This research proposal aims to analyze This research proposal aims to analyze the academic documentación of 4 studies on the relationship between family violence and academic performance in students. For this reason, we worked with a qualitative method, of a documentary nature, where there are sources of information such as books, web pages, among others, with a sample of 20 studies carried out regarding family violence and academic performance in young people.